Optimized icariin cubosomes exhibit augmented cytotoxicity against SKOV-3 ovarian cancer cells - A. Fahmy, Usama; Fahmy, Omar; A. Alhakamy, Nabil (MDPI, 2021)
Clinical application of icariin (ICA) is limited, despite its activity against cancer growth, because of the low solubility of ICA in an aqueous environment. Therefore, the present study attempted to develop and optimize ICA-loaded cubosome delivery and to explore its efficacy and possible mechanism of action against ovarian cancer. The optimization of the cubosome formulation was performed using the Box‒Behnken statistical design; during the characterization, the particle sizes were in the range of 73 to 183 nm and the entrapment efficiency was 78.3% to 97.3%. Optimized ICA-loaded cubosomes (ICA-Cubs) exhibited enhanced cytotoxicity and apoptotic potential, compared with ICA-raw, against ovarian cancer cell lines (SKOV-3 and Caov 3). The optimized ICA-Cubs showed a relatively non-cytotoxic effect on normal EA.hy926 endothelial cells. Further analysis of cell cycle arrest suggested a potential role in the pre-G1 and G2/M phases for ICA-Cubs in comparison with ICA-raw. ICA-Cubs increased the generation of reactive oxygen species (ROS) and the overexpression of p53 and caspase-3 in the SKOV-3 cell line. In conclusion, the cubosomal delivery of ICA might provide a prospective approach towards the superior control of ovarian cancer cell growth. Its improved efficacy compared with that of the free drug might be due to the improved solubility and cellular permeability of ICA.